Connected objects in health : risks, uses and perspectives - Beyala, Laure (Health industrialization set., 2017)
Connected objects today present a range of opportunities in medicine. We live in a new digital era where the monitoring and analysis of one's own health information no longer belongs solely to the realm of science fiction. The success of these new devices resides in their usage, which integrates seamlessly into the daily life of the user in order to continually collect the maximum amount of data. These medical connected devices therefore constitute a new hope in transforming user experience as well as the care pathway. They offer a better level of support and a better quality of life for those suffering from chronic illnesses or mental, sensorial or physical disabilities. However, these solutions also pose systematic problems, especially regarding the risks linked to their usage. This book presents a cartography which clearly details all the potential risk scenarios linked to the usage of connected devices as well as the actions which should be undertaken to promote balanced governance and guarantee the development of high-quality medical devices.